Differentiated selection method to admission in medical education - Gulshat Kemelova; Raushan Dosmagambetova; Viktor Riklefs; Aida Kassatova (National Scientific Medical Center, 2018)
The aim: To compare the results of multiple mini-interviews with the results of medical students' achievements after the completion level of study. Methods: The study was conducted to determine the efficacy, validity, and reliability of the multiple mini-interview methods for differential selection and admission to medical education organizations. The study assessed the ability to learn with the definition of the professional suitability of students of 1 year of study (n = 491) with the help of multiple mini-interviews, followed by their academic achievements for two years, evaluated the final results for the Grade Point Average after each stage of the study. Results: Analysis of the results showed that the multiple mini-interviews are a suitable method to evaluate candidates' ability to study in medicine, which assesses a creative thinking, communication skills, and a personal behavior. Candidates with high scores of the United National Testing and multiple mini-interviews confirm their abilities with academic achievements, however, they account for a one-third of the total. 12% of students, who have left the university at their own will, had average United National Testing results and low multiple mini-interviews scores, which indicated their low motivation to study in medicine and lack of willingness to overcome learning difficulties. Annually more than 15% of students re-study some of the disciplines, and this is also due to the fact that they do not study with the curriculum. The high results of multiple mini-interviews matched with the high results of United National Testing and educational achievements in only 23.6% of the total number of candidates, which show the reliability and applicability of the method studied. Conclusion: Multiple mini-interview is the most suitable method for qualitative differentiated selection and admission of applicants to medical universities, which allows to evaluate and predict professional suitability and to minimize the number of "casual" students in medicine. Multiple mini-interview is a reliable and acceptable method and is recommended to be introduced as an additional exam for admission to medical universities.